2007
DOI: 10.1017/s1742170507001639
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of mulching technology as an alternative to slash-and-burn farming in eastern Amazon: A cost–benefit analysis

Abstract: This paper addresses the question as to whether it is profitable to apply a mechanical mulching technology (MT) in the Bragantina region of Brazil and assesses the technology's feasibility as an alternative to the slash-and-burn practices of the Amazon. Using empirical data collected from a prototype assessment and a few secondary sources, the paper employs a cost-benefit analysis of 'with' and 'without' technology cropping systems (plots that applied the technology are compared with those that did not) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…These systems require, however, a considerable initial capital, which is frequently not available to the smallholder farmers in the Eastern Amazon region. Moreover, it may take several years for farmers to begin making a profit from these systems above that achievable with the traditional slash-and-burn shifting cultivation systems (Lojka et al, 2008;Mburu et al, 2007). In this context, and to reduce the contribution of smallholder farmers to deforestation, there is an urgent need for supporting more sustainable production systems through local and national public policies (Tremblay et al, 2015).…”
Section: Cassava Root Yield Gapmentioning
confidence: 99%
“…These systems require, however, a considerable initial capital, which is frequently not available to the smallholder farmers in the Eastern Amazon region. Moreover, it may take several years for farmers to begin making a profit from these systems above that achievable with the traditional slash-and-burn shifting cultivation systems (Lojka et al, 2008;Mburu et al, 2007). In this context, and to reduce the contribution of smallholder farmers to deforestation, there is an urgent need for supporting more sustainable production systems through local and national public policies (Tremblay et al, 2015).…”
Section: Cassava Root Yield Gapmentioning
confidence: 99%
“…Figure 6 Schematic illustrating the conceptual framework derived from GEF project for the development of the alternatives to slash-and-burn (Brady, 1996) In general, there are two main methods for alternatives to slash-and-burn, namely land preparation, and landuse systems. In terms of land preparation, a few of its approaches include addition of cover on top of the soil/mulching (Eastmond & Faust, 2006;Kato et al, 1999;Mburu et al, 2007), improved forest conversion , mechanized land preparation (Denich et al 2004, Mburu et al, 2007Panosso et al, 2009;Reichert et al, 2014), and simple slash-and-char system (Liang et al, 2018). Eastmond and Faust (2006) had mentioned that according to SEMARNAT, the federal environmental protection agency of Mexico, the application of fire in agriculture can primarily yield conflagration.…”
Section: Recommendations For Alternative Practicesmentioning
confidence: 99%
“…This confirms that the fire-free agriculture can be applicable to some crops, and this may result in the reduced adoption of slash-and-burn practices in agriculture. Mburu et al (2007) revealed that mechanical mulching technology in Bragantina area of Brazil was generally profitable financially and economically. However, in order to make it a feasible alternative to the slash-and-burn practices in eastern Amazon, there are a few criteria to be met, one of which is abandonment of the single cropping cycle and the selection of profitable crop combinations for agriculture.…”
Section: Recommendations For Alternative Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lantana mulching gave greater financial returns and P-use efficiency than polythene mulching in wheat (Sharma & Parmar 1998). Mulching technology has been found to be profitable, both financially and socially, in the eastern Amazon region of Brazil because it was able to produce yields that were high enough to offset the costs (Mburu et al 2007). The economic benefits of mulching considered only the increase in productivity of crops; the improvements in physico-chemical properties of soil were not accounted for.…”
Section: Economicsmentioning
confidence: 99%